Primary stability of implant placement and loading related to dental implant materials and designs: A literature review - Yu-Che Huang; Yen-Chang Huang; Shinn-Jyh Ding (Elsevier, 2023)
A variety of implant placement and loading protocols are identified, ranging from immediate implant placement on the day of extraction to delayed placement for at least 6 months after complete healing. The method of assessment of implant placement and loading plays an important role in the implantation. The expected clinical outcomes depend largely on multiple factors, such as the macroscopic design of the implant, surgical technique, and the quality and quantity of local bone in contact with the implant, which would be described in detail. The purpose of this literature review was to explore the relationship between the factors influencing the implant placement stability and implant design. By understanding the original appearance of implant design and the stability requirements of implant placement, it is hoped that more research in the future can meet the needs of dentists and patients.